If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -10y = 3 Solving 9x + -10y = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10y' to each side of the equation. 9x + -10y + 10y = 3 + 10y Combine like terms: -10y + 10y = 0 9x + 0 = 3 + 10y 9x = 3 + 10y Divide each side by '9'. x = 0.3333333333 + 1.111111111y Simplifying x = 0.3333333333 + 1.111111111y
| 3s-8=9 | | 5n+3n+n+5=26 | | 5y=12x-5 | | 3x+9=56-4x | | 3a-b=1 | | a+10=27 | | 10x+1y=8 | | -5(1-5)+(-8x-2)=4x-8x | | -1/2+w=3/5 | | (x-6)+x= | | 23+2x=13 | | 3(2c+3)=2(3c-4) | | 6n-10+4n=-18+10n+14 | | 51-3x=6x+23 | | a+3b=7 | | 13+2x=x+25 | | 3x-18/15 | | 5=4n-6 | | 3w-40-2w+60+w= | | 13x+12=38 | | 4n-6=14 | | 15-12x=51 | | f(x)=10-4x | | 4x+18=x+33 | | -31/3b+b | | 8+6a=-28+24 | | 2(3.5x+6)=2.5x-2 | | 2=9x | | 1/2x+4=-3 | | 0.6x=-7.2 | | x^2+y^2-9= | | (x-3)(3x+5)=0 |